INNOVATION OF WASTE MANAGEMENT WASTE TO ENERGY TECHNOLOGY BASED IN MALANG CITY (SUPITURANG FINAL DISPOSAL SITE STUDY) - Amalia Rahmadani Anwar (Departemen Administrasi Publik, Universitas Diponegoro, 2023)
City waste continues to increase resulting from every human activity. The research objective is related to waste management innovation using waste to energy technology in the use of waste at the Supit Urang TPA. Gas emissions released by piles of rubbish piled up in final disposal sites not only try to reduce and prevent humans, the environment and the earth from being damaged, but also use renewable energy. Descriptive qualitative research method. Data collection techniques through documentation, interviews and field study observations. Data analysis techniques involve collecting data from field studies (written and verbal), researching, reducing and then drawing conclusions. Using Roger's innovation theory. The results of the research show that the waste problem is not only borne by the government. Waste management must be completed from upstream to downstream, namely from community settlements to the final disposal site. The renewal of the management system for waste utilization has been in effect since the decentralization of the program from the Ministry of Public Works and Public Housing to the Environmental Service to build the latest technology-based waste disposal system. German assistance in infrastructure development is one of the successful factors in implementing the renewal of the Supit Urang landfill waste utilization system. The output of the waste to energy program is electrical energy and gas. Increasing energy production from landfills provides benefits to the community and also local governments as energy producers. Keyword: Innovation, Waste Management, Waste into Energy